Increased Sensitivity to Serotonin Syndrome in Cerebral Palsy - Adam Schindzielorz (Case Reports in Psychiatry)
Serotonin syndrome is characterized by symptoms of neuromuscular and autonomic excitation and altered mental status. It is most often drug induced with antidepressants being the main precipitants. However, other classes have been implicated as well including antipsychotics, antiemetic and pain medications, and lithium. The syndrome is typically induced by the combination of two or more serotonergic agents; however, there have been instances of serotonin syndrome occurring while a patient is on a single medication. The literature is limited regarding the study of risk factors associated with the production of serotonin syndrome while on only monotherapy or otherwise atypically causative agents. One such risk factor may be underlying neuromuscular pathology. This study is the first case series to our knowledge reporting two separate cases of serotonin syndrome being induced in patients with cerebral palsy as an underlying common factor.